2016
DOI: 10.18632/oncotarget.11706
|View full text |Cite
|
Sign up to set email alerts
|

HuR silencing elicits oxidative stress and DNA damage and sensitizes human triple-negative breast cancer cells to radiotherapy

Abstract: HuR is an mRNA-binding protein whose overexpression in cancer cells has been associated with poor prognosis and resistance to therapy. While reports on HuR overexpression contributing to chemoresistance exist, limited information is available on HuR and radioresistance especially in triple-negative breast cancer (TNBC).In this study we investigated the role of HuR in radiation resistance in three TNBC (MDA-MB-231, MDA-MB-468 and Hs578t) cell lines. Endogenous HuR expression was higher in TNBC cells compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 69 publications
0
71
2
Order By: Relevance
“…Total cells lysates prepared from lung tumor and normal cells receiving various treatments were subjected to Western blotting as previously described32 and is briefly illustrated in supplemetry section 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total cells lysates prepared from lung tumor and normal cells receiving various treatments were subjected to Western blotting as previously described32 and is briefly illustrated in supplemetry section 3.…”
Section: Methodsmentioning
confidence: 99%
“…Double strandbreaks (DSBs) induced by free-Dox, NanoDox and nanosomes were determined by Comet assay (CometAssay ® kit; Trevigen, Inc., Gaithersburg, MD) as previously described32. The detail of the comet assay is outlined in supplementary section 4.…”
Section: Methodsmentioning
confidence: 99%
“…As cancers present with ever-increasing heterogeneity, siRNA-based therapy is increasingly being explored in combination with chemo- [127], [128], immune- [129]–[131], radiation- [132]–[134], and photodynamic therapies [135]–[137]. While gene silencing using siRNA improves the sensitivity of drug resistant cancer to chemotherapeutics [127] siRNA mediated downregulation of immunosuppressive genes enhances the sensitization of cancer cells towards T cell-mediated killing [129].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…While gene silencing using siRNA improves the sensitivity of drug resistant cancer to chemotherapeutics [127] siRNA mediated downregulation of immunosuppressive genes enhances the sensitization of cancer cells towards T cell-mediated killing [129]. Reports also suggest that siRNA based silencing of specific genes enhances radiosensitization of cancer cells [133], [134]. In contrast, downregulation of certain genes protect normal tissues from harmful effect of radiation [132].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Recent studies from our laboratory demonstrated that HuR downregulation inhibited cell growth in non-small cell lung cancer (NSCLC) in vitro and altered the cells’ ability to undergo migration and invasion [12,15]. Further, we recently showed HuR inhibition radiosensitized human breast cancer cells [16]. All of these studies indicate HuR is a molecular target for cancer therapy and advancing preclinical testing of HuR-targeted therapies could ultimately lead to clinical testing.…”
Section: Introductionmentioning
confidence: 99%